Numerical investigation of the nanoparticle volume fraction effect on the flow, heat transfer, and entropy generation of the Fe3 O4 ferrofluid under a non-uniform magnetic field - Hosseinzadeh, Fazel (Strojniški vestnik, 2016)
This paper presents research on the forced flow convective heat transfer of a ferrofluid (water and Fe 3 O 4 ) in a horizontal two-dimensional channel under the influence of a 2D non-uniform magnetic field, which is applied through a line dipole. The governing equations of this research include continuity, momentum, energy and entropy generation, which are solved with a finite volume technique. Moreover, a grid- independent test and the validation of numerical results are carried out. The effect of the Fe 3 O 4 volume fraction (1 vol % to 6 vol %) on the hydro-thermal characteristics of the ferrofluid flow and entropy generation is studied. Numerical results show that the flow pattern is highly changed, because the kelvin body force overcomes the viscous force by increasing the volume fraction under applied magnetic field. Furthermore, the average wall friction factor increases linearly. The average Nusselt number ( Nu ) increases with the increase of the Fe 3 O 4 volume fraction, so that Nu increases by 51.1 % in comparison to the base fluid at 6 vol %. It is observed that the Nusselt number ratio (NUR) at 6 vol % is enhanced by 10.4 % whereas the entropy generation ratio (NSR) is increased by only 6.2 % compared to 4 vol %. According to the results of the study, it is concluded that using volume fractions between 4 vol % to 6% would result in an observable improvement in convective heat transfer while enhanced entropy generation is relatively small, so it is thermodynamically affordable
Keywords: ferofluidi; končni volumni; magnetno polje; ustvarjanje entropije; volumski delež nanodelcev